Manajemen Kurikulum Merdeka dalam Meningkatkan Mutu Pendidikan di SMP Negeri 2 Ploso Jombang - Ni'mah, Devi Khoirun; Sirojudin, Didin (ISLAMIKA, 2024)
The curriculum for Merdeka Learning has advanced to the point where it may be classified as under development. Right now, the government is emphasizing how important it is to use it in all educational settings. The Republic of Indonesia's Minister of Education and Culture, Nadiem Makarim, was there, and his presence encouraged the idea for curriculum adjustments, namely the autonomous learning curriculum. According to the curriculum concept known as "merdeka learning," students must be independent. The administration's main goal is to improve education, and several initiatives have been put in place for that purpose.1.) Gain an understanding of the Curriculum Merdeka's management in order to enhance the educational quality at SMP Negeri 2 Ploso. 2.) Understanding the elements that help and hinder the management of the Merdeka curriculum to raise the standard of instruction at SMP Negeri 2 Ploso. This type of research is called field research, which is conducted on-site at the subject, mostly with the aim of gathering data and other information. In the meantime, this research is qualitative in character, that is, it takes the form of a research technique that yields descriptive data. The principal's choice about the curriculum merdeka's implementation was based on the study findings intended to enhance the educational quality at SMP Negeri 2 Ploso in the process of creating the curriculum. Subsequently, the curriculum merdeka manager collaborated with the development and quality assurance teams to establish the school's operational curriculum, which was then submitted to the Ministry of Education and Culture's office (Kemendikbud) as a school implementing the curriculum merdeka. We may therefore conclude that the independence curriculum was prepared based on the principal's choice on its implementation in order to raise the standard of instruction at SMP Negeri 2 Ploso. Analyze the work that instructors and other teaching staff members do during class hours.